Conjugate of M-N Anti Fuzzy Soft Subgroups - S. Rumenaka, M. Kaliraja (International Journal of Control and Automation, 2020)
In this paper, we have discussed the concept of a conjugate of M-N anti fuzzy soft subgroup and define the M-N anti fuzzy soft middle cosets.  It is some elementary properties are discussed.